Sulfate is Incorporated into Cysteine to Trigger ABA Production and Stomatal Closure. Issue 12 (11th December 2018) - Batool, Sundas; Uslu, Veli Vural; Rajab, Hala; Ahmad, Nisar; Waadt, Rainer; Geiger, Dietmar; Malagoli, Mario; Xiang, Cheng-Bin; Hedrich, Rainer; Rennenberg, Heinz; Herschbach, Cornelia; Hell, Ruediger; et al.
Abstract : Comprehensive genetic analysis uncovers mechanistic insights into sulfate-induced activation of ABA biosynthesis to close stomata. Abstract: Plants close stomata when root water availability becomes limiting. Recent studies have demonstrated that soil-drying induces root-to-shoot sulfate transport via the xylem and that sulfate closes stomata. Here we provide evidence for a physiologically relevant signaling pathway that underlies sulfate-induced stomatal closure in Arabidopsis ( Arabidopsis thaliana ). We uncovered that, in the guard cells, sulfate activates NADPH oxidases to produce reactive oxygen species (ROS) and that this ROS induction is essential for sulfate-induced stomata closure. In line with the function of ROS as the second-messenger of abscisic acid (ABA) signaling, sulfate does not induce ROS in the ABA-synthesis mutant, aba3 - 1, and sulfate-induced ROS were ineffective at closing stomata in the ABA-insensitive mutant abi2 - 1 and a SLOW ANION CHANNEL1 loss-of-function mutant. We provided direct evidence for sulfate-induced accumulation of ABA in the cytosol of guard cells by application of the ABAleon2.1 ABA sensor, the ABA signaling reporter ProRAB18 : GFP, and quantification of endogenous ABA marker genes. In concordance with previous studies, showing that ABA DEFICIENT3 uses Cys as the substrate for activation of the ABSCISIC ALDEHYDE OXIDASE3 (AAO3) enzyme catalyzing the last step of ABA production, we demonstrated that assimilation of sulfate into Cys is necessary for sulfate-induced stomatal closure and that sulfate-feeding or Cys-feeding induces transcription of NINE-CIS-EPOXYCAROTENOID DIOXYGENASE3, limiting the synthesis of the AAO3 substrate. Consequently, Cys synthesis-depleted mutants are sensitive to soil-drying due to enhanced water loss. Our data demonstrate that sulfate is incorporated into Cys and tunes ABA biosynthesis in leaves, promoting stomatal closure, and that this mechanism contributes to the physiological water limitation response.